Impact of Isothermal Layering on the Stability of Saline Soil Subgrade in Cold Regions. (4th April 2022) - Zhang, Yu; Chen, Xuerui; Zou, Meisi; Tian, Runze; Hou, Yunlong; Han, Bingbing
Abstract : In order to determine the influence of heat on the stability of the saline soil subgrade slope in cold regions. Firstly, four typical representative saline soils were selected as subgrade fillers, and geotextiles were added at the bottom of the subgrade as a study subject. A two-dimensional numerical model for the temperature field of subgrade soil was established based on COMSOL Multiphysics. Secondly, combined with the main strength parameters of subgrade soil at different temperatures, an isothermal stratification-strength parameter function calculation model was proposed. Then, the SLOPE/W module in GeoStudio is used to stratify the established subgrade model according to isotherms and calculate the stability safety factor of saline soil subgrades in cold regions under different months, slopes, and subgrade heights, respectively. Finally, the influence of submergence at the foot of the slope on the stability of the subgrade slope is discussed. The results show: After the cold season coming, with the decreasing of temperature, the stability of HC-1 and HC-2 saline soil subgrade slope increased to different extents when the ground temperature dropped to -10°C. When the local temperature dropped below -10°C, the stability has slight decline; CS-1 and CS-2 saline soil subgrade in the ground temperature dropped to 10°C (HC-1 and HC-2 denote two groups of saline soil with high chloride-salt content (≥15%) and low sulfate salt content (≤0.5%), whereas CS-1 and CS-2 denote two groups of saline soil with low chloride-salt (≤5%)), the slope stability was significantly improved, and the stability of CS-1 increases slightly with further decrease in temperature.